Pemberdayaan Ekonomi Warga Lewat Program Spanduk Umkm Dan Plang Gang Kreatif Dalam Mewujudkan Ekonomi Yang Inovatif - Rizki Adiah Putra; Devin Aditia Pratama; Della Eka Verlina; Rega Ova Kencana; Suci Anggelica Arci Panjaitan; Aura Puspita Ramadhani; Hermawansa Hermawansa; Mujiono Mujiono (Universitas Dehasen Bengkulu, 2026)
The Creative Alley Signboard and MSME Banner Program is a strategic initiative aimed at empowering local communities through the optimization of local economic potential. This program seeks to strengthen neighborhood identity, promote micro, small, and medium enterprises (MSMEs), and create a creative promotional space within the community. By designing banners and alley signboards that integrate aesthetics and local wisdom, the program fosters collaboration among entrepreneurs, local government, and residents. The outcomes include increased visibility of MSME products, enhanced entrepreneurial motivation, and the transformation of neighborhoods into more attractive and productive spaces. This initiative exemplifies how creativity-based and community-driven empowerment can foster an innovative, competitive, and sustainable local economy.